2021
DOI: 10.3389/fpsyg.2021.766392
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistency Congruence and Smartphone Addiction in Adolescents: The Mediating Role of Subjective Well-Being and the Moderating Role of Gender

Abstract: Adolescent smartphone addiction has increasingly attracted the attention of scholars because of the widespread use of internet technology in educational environments. In addition, previous studies have found that there is a complex relationship between smartphone addiction and self-consistency congruence, and subjective well-being. This research was conducted to examine whether subjective well-being would mediate the relation between self-consistency congruence and adolescent smartphone addiction, and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…The results of the meta-analysis showed that SA was highly negatively correlated with subjective well-being, weakly negatively correlated with life satisfaction and positive emotions, and highly positively correlated with negative emotions. It shows that individuals with SA have lower subjective well-being, life satisfaction, and positive emotions, but higher negative emotions, which is consistent with most previous studies (Wang and Zhang, 2015;Yang et al, 2019;Li et al, 2021). This may be because individuals with low subjective well-being received less social support in real life, while the online social support provided by smartphones can compensate for the lack of social support in real life and help them escape the pain of the real world (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the meta-analysis showed that SA was highly negatively correlated with subjective well-being, weakly negatively correlated with life satisfaction and positive emotions, and highly positively correlated with negative emotions. It shows that individuals with SA have lower subjective well-being, life satisfaction, and positive emotions, but higher negative emotions, which is consistent with most previous studies (Wang and Zhang, 2015;Yang et al, 2019;Li et al, 2021). This may be because individuals with low subjective well-being received less social support in real life, while the online social support provided by smartphones can compensate for the lack of social support in real life and help them escape the pain of the real world (Gao et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…A very recent study by Y. Li et al. (2021) suggested that self‐consistency congruence negatively predicts adolescent SPA and hence, gender might modulate the interaction between self‐concordance and well‐being in adolescents. Some of these interactions may be embedded in distinct cultural backgrounds (Ha & Hwang, 2014; Ko et al., 2005; Y. Li et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(2021) suggested that self‐consistency congruence negatively predicts adolescent SPA and hence, gender might modulate the interaction between self‐concordance and well‐being in adolescents. Some of these interactions may be embedded in distinct cultural backgrounds (Ha & Hwang, 2014; Ko et al., 2005; Y. Li et al., 2021). Very little is known at present whether gender‐related neurodevelopmental trajectories may yield further increased risk for SPA.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective well-being is a psychological state, which is an individual’s satisfaction with his psychological state and the overall assessment of the positive and negative emotions he has experienced ( Li et al, 2021b ). Subjective well-being also reflects their social functioning and adaptation status ( Zhang et al, 2022 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As research has found, subjective well-being hurts adolescents’ Internet addiction behavior. When the happiness of individuals decreases, they will experience strong negative emotions, and their negative emotions can positively predict their smartphone addiction behavior ( Li et al, 2021b ). Research showed that individuals with traditional gender role attitudes are more likely to have greater psychological distress and cause work–family conflict ( Hajar et al, 2010 ; Bornatici and Heers, 2020 ; Hu et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%